Gender Differences in Earnings and Leadership: Recent Evidence on Causes and Consequences - Mario Macis; Mirco Tonin (ifo DICE Report, 2017)
Women's labour market outcomes have improved substantially in the past decades, both in absolute terms and relative to men, in the United States and Western European countries as well as in several other countries around the world. Specifically, gender gaps have narrowed considerably (and in several cases disappeared) in human capital accumulation (educational attainment), labour force participation, hours of work and occupation. Claudia Goldin referred to this phenomenon as a 'grand gender convergence' (Goldin 2014). Yet, gender gaps in earnings and leadership still persist. Women earn substantially less than men and are under-represented in leadership positions in firms and organisations more broadly. The presence and persistence of gender gaps in earnings and leadership is cause for great concern for both reasons of social justice and efficiency, to the extent that the gender imbalances reflect a sub-optimal allocation of human capital in firms and in the economy. In this article, we focus on the causes and consequences of female-male gaps in earnings and representation at the top of organisations. Gender gaps in wages and leadership are one of the most researched topics in labour economics and beyond. Rather than attempting to summarise the vast literature on these subjects, we present a selective discussion of recent empirical work in an attempt to highlight recent findings on causes and consequences of gender gaps in the labour market and to discuss the main knowledge gaps and what we believe are some of the most promising areas for future research.1 Most of the papers we focus on refer to the United States, but the trends and patterns described are likely to apply more broadly.
Keywords: J16; 330; Lohnstruktur; Erwerbsverlauf; Geschlechterdiskriminierung; Weibliche Führungskräfte; Arbeitsangebot